The Pressure Characteristics of the Released Gases from Sand Cores - Mádi, Laura Johanna; Budavári, Imre; Varga, László (International Journal of Engineering and Management Sciences, 2020)
The core packages used for the production of castings are generally made from cores of different quality (no- bake phenol, HB-phenol, and HB-furan) and resin quantity, to meet the various requirements for the casting. In our research, the effect of the amount of resin on the pressure of the gases evolved from the cores was investigated. Experiments have shown that increasing the amount of resin has a different effect on different binder systems.